Analytical Profiling of Heavy Metals Contamination in soils, Dismantling Dust, and Rubber Samples in Karachi City Using AAS, WD-XRF, and SEM Technique - Abdul Rafeeq; Syed Azhar Ali; Asad Khan Tanoli; Naseem Akhter; Ghulam Raza (CV. Literasi Indonesia, 2021)
The concentrations of Cd, Cr, Cu, Fe, Ni, Pb, & Zn were determined in the samples of soil, dismantling dust and rubber collected from the electronic waste dumping site of Shershah market and rubber from the Local market of Karachi city Pakistan. The city e-waste dumping and dismantling sites toxicity were not conducted before using modern techniques. The subsequent data of the heavy metals concentration were obtained using Atomic Absorption Spectrometry (AAS), Scanning Electron Microscopy (SEM), and Wavelength Dispersive- X-Ray Fluorescence Spectrometry (WD-XRF). Cu, Pb, and Zn were found as 133.17, 104.53 & 113.26 in soil, whereas in dismantling dust Pb & Zn were remained 10.56 and 12.65 mg/kg similarly. The China toy particle analysis by SEM was resulting metallic trend as Fe > Zn > Pb > Cd > Ni > Cr. The estimated data were compared with the levels allowed by the Pakistan Environmental Protection Agency (Pak-EPA) and the United States Environmental Protection Agency (USEPA). The maximum allowable limit for Cd is 3; Cr, Cd, and Pb are 100 for Ni is 50 and 300 mg/kg for Zn. The presence of these heavy metals from e-waste dumping would become soon a significant reason to cause serious health problems for the nearby residents and as well as city too. It has been concluded that the dumping of e-waste is the major source of contamination of heavy metals in the studied media. It is recommended that the e-waste must be recycled formally to prevent the soil from being polluted. .